Predicting buildings construction cost overruns on the basis of cost overruns structure - Car-Pušić, Diana; Tijanić, Ksenija; Marović, Ivan; Mlađen, Marko (Scientific Review Engineering and Environmental Sciences (SREES), 2020)
In construction practice, contractually agreed costs are often exceeded, which interferes with the sustainable realization of construction projects. The research described in this paper covers 24 new construction, renovation and reconstruction projects in the Republic of Croatia realized in the years 2006 to 2017, in order to analyse the occurrence of cost overruns more precisely with regard to the source of the overruns. It was found that additional work is the main source of cost overruns: firstly, additional work as a result of the client’s change orders and then unforeseen construction work as a result of unforeseen circumstances. As for the additional works, they are carried out at the client’s request and are not necessary for the safety and stability of the building. Using linear regression and “soft computing” methods, the possibility of modelling the relationship between contractually agreed and realized construction costs with satisfactory accuracy was tested. The model with the values of the natural logarithms of the variables, modelled according to the time–cost model of Bromilow, proved to be of the highest accuracy.